The significance of chronological order of sūrahs on antioxidants in makkiyah context - Latifah Abdul Majid; Wan Nasyrudin Wan Abdullah; Nurul Mukminah Zainan Nazri (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this paper was to analyze the significance of chronological order of sūrahs on antioxidants in makkiyah context. This paper answered the query on the chronological order of sūrahs on antioxidants in makkiyah context which possesses particular significance. This paper primarily focuses on the sūrahs which were revealed in the Makkan period to facilitate a better understanding of the antioxidants in this context. This is a qualitative study and the approach is content analysis. Data collected through the methods of content and document analysis will be thematically analyzed through the usage of descriptive and analytical methods. Findings demonstrate that the sūrahs on antioxidants in makkiyah context were revealed in three phases of the Makkan period which are: early years, middle years, and last years of Makkan period. The implication of the study establishes that every phase in the Makkan period denotes different circumstances. Hence, the antioxidants that are stated during that phase suit its situation. The foods that are stated in the three phases of Makkan period contain antioxidant compounds and the Makkan society has a variation of antioxidants in their diet as well as the situations in each phase taught lessons such as gratitude and patience. Thus, the Muslim society or any individual may ponder upon these lessons and contemplate on the antioxidants as a proof of the scientific miracles in the Quran (Al-I’jāz Al-‘Ilmī) and as the best dietary guidance.